Common risk allele in aromatic antiepileptic-drug induced Stevens-Johnson syndrome and toxic epidermal necrolysis in Han Chinese - Hung, Shuen-Iu; Chung, Wen-Hung; Liu, Zhi-Sheng; Chen, Chien-Hsiun; Hsih, Mo-Song; Hui, Rosaline Chung-yee; Chu, Chia-Yu; Chen, Yuan-Tsong (Pharmacogenomics, 2010)
Compared with other categories of drugs, such as antibiotics and NSAIDs, antiepileptic therapies are associated with a high incidence of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). We previously reported that carbamazepine (CBZ)-SJS/TEN is strongly associated with the in Han Chinese, which has been confirmed in other Southeast Asian countries where the allele is prevalent. Here, we extend the study of HLA susceptibility to three different antiepileptic drugs, phenytoin (PHT), lamotrigine (LTG) and oxcarbazepine (OXC), which have structure similarity to CBZ. We carried out a case-control association study. We enrolled 26 PHT-, six LTG- and three OXC-induced SJS/TEN patients, 113 PHT-tolerant and 67 LTG-tolerant subjects who were on the drug, respectively, for more than 3 months without the adverse reactions, and 93 normal subjects from the general population. The , , and genotypes were determined. We found that HLA-B*1502 was present in eight out of 26 (30.8%) PHT-SJS/TEN (OR: 5.1; 95% CI: 1.8-15.1; p = 0.0041), two out of six (33%) LTG-SJS (odds ratio [OR]: 5.1; 95% CI: 0.8-33.8; p = 0.1266) and three out of three (100%) OXC-SJS (OR: 80.7; 95% CI: 3.8-1714.4; p = 8.4 × 10 ) patients. In addition, , and also showed an association with PHT-SJS/TEN (p = 0.0128-0.0281; OR: 3.0-4.3). Our results indicate that OXC, PHT and LTG, which possess an aromatic ring just as CBZ does, when causing SJS/TEN, share a common risk allele. Aromatic antiepileptic drugs causing SJS/TEN in carriers may act on a similar pathogenetic mechanism, although other genetic/nongenetic factor(s) may also contribute to the pathomechanism of the disease. We suggest that aromatic antiepileptic drugs, including CBZ, OXC and PHT, should be avoided in the carrier and caution should also be exercised for LTG.